Continuing education and strengthening the performance of the community role of serumista nurses - Ruiz Aquino, Mely (2020)
Objective. To demonstrate the effectiveness of continuing education in strengthening the performance of the community role of serumista nurses of Regional Council XII in Huánuco. Methodology. It was an experimental-longitudinal research, with two groups (experimental and control), composed of 58 nurses in each group, selected by random probability sampling. Prior to the continuing education program, a previously validated community role performance questionnaire was applied. Ethical considerations were taken into account. Student's t-test was applied for inferential analysis. Results. It was observed that before the intervention, only 1.7% (1) of the experimental group had high-level community role performance, 89.7% (52) of good level and 8.6% (5) of poor level. On the other hand, 98.3% (57) of the control group had a good level and 1.7% (1) had a poor level. After the intervention, 86.2% (50) of the experimental group showed a high level and 13.8% (8) a good level. Only 1.7% (1) of the control group reached a high level and 98.3% (57) a good level. The existence of significant differences between the averages of the moments and study groups was verified [t = -19.301; p = 0.000], being higher in the experimental group, therefore it is admitted that continuing education strengthens the performance of the community role of serumista nurses in the experimental group. Conclusion. Continuing education strengthens the community role performance of serumista nurses, showing significant differences in the averages between groups and during the post-test [t = 15.601; p = 0.000].